Compact and modular system architecture for a nano-resonator-mass spectrometer - Reynaud, Adrien; Trzpil, Wioletta; Dartiguelongue, Louis; Çumaku, Vaitson; Fortin, Thomas; Sansa, Marc; Hentz, Sebastien; Masselon, Christophe (Frontiers in Chemistry, 2023)
Mass measurements in the mega-to giga-Dalton range are essential for the characterization of natural and synthetic nanoparticles, but very challenging to perform using conventional mass spectrometers. Nano-electro-mechanical system (NEMS) based MS has demonstrated unique capabilities for the analysis of ultra-high mass analytes. Yet, system designs to date included constraints transferred from conventional MS instruments, such as ion guides and high vacuum requirements. Encouraged by other reports, we investigated the influence of pressure on the performances of the NEMS sensor and the aerodynamic focusing lens that equipped our first-generation instrument. We thus realized that the NEMS spectrometer could operate at significantly higher pressures than anticipated without compromising particle focusing nor mass measurement quality. Based on these observations, we designed and constructed a new NEMS-MS prototype considerably more compact than our original system, and which features an improved aerodynamic lens alignment concept, yielding superior particle focusing. We evaluated this new prototype by performing nanoparticle deposition to characterize aerodynamic focusing, and mass measurements of calibrated gold nanoparticles samples. The particle capture efficiency showed nearly two orders of magnitude improvement compared to our previous prototype, while operating at two orders of magnitude greater pressure, and without compromising mass resolution.